REVOLUTIONIZING MEDICINE: A COMPREHENSIVE REVIEW OF MODERN DIAGNOSTIC TECHNOLOGIES - Asatullyev Rustam Baxtiyorovich,; Qilichbayeva Malikabonu Uchqunjon qizi, (TADQIQOTLAR, 2026)
Abstract:  Diagnostic  technologies  are  the  cornerstone  of  modern  medicine, enabling the accurate detection, characterization, and monitoring of human diseases. This article provides a systematic overview of major diagnostic modalities, including medical  imaging  (X-ray,  computed  tomography,  magnetic  resonance  imaging, ultrasound, and nuclear medicine), molecular diagnostics (polymerase chain reaction, next-generation sequencing, and biosensors), point-of-care technologies, and emerging fields such as liquid biopsy and artificial intelligence-assisted diagnosis. The article discusses  the  principles,  clinical  applications,  advantages,  and  limitations  of  each technology. Special attention is given to the role of diagnostic technologies in early disease detection, personalized medicine, and infectious disease outbreaks, including the  COVID-19  pandemic.  The  review  concludes  with  an  analysis  of  current challenges—such as cost, accessibility, and data integration—and future directions, including lab-on-a-chip devices and wearable diagnostics.